2017
DOI: 10.1016/j.celrep.2017.09.030
|View full text |Cite
|
Sign up to set email alerts
|

Host MicroRNAs-221 and -222 Inhibit HIV-1 Entry in Macrophages by Targeting the CD4 Viral Receptor

Abstract: Macrophages are heterogeneous immune cells with distinct origins, phenotypes, functions, and tissue localization. Their susceptibility to HIV-1 is subject to variations from permissiveness to resistance, owing in part to regulatory microRNAs. Here, we used RNA sequencing (RNA-seq) to examine the expression of >400 microRNAs in productively infected and bystander cells of HIV-1-exposed macrophage cultures. Two microRNAs upregulated in bystander macrophages, miR-221 and miR-222, were identified as negative regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
71
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(76 citation statements)
references
References 51 publications
5
71
0
Order By: Relevance
“…Our finding is in agreement with a previous study where miR-630 was reported as a biomarker in chronic progressors of HIV-1 [38]. Interestingly, our HM exosomal miRNA data from the South Africa cohort where HIV-1 infected women were carrying HIV-1 load < 1 year (data not shown) showed downregulation of these miRNAs identified in the current study (Table 2 & Suppl Table 1) and correlated with a recent report where it was shown that acute HIV-1 leads to downregulation of miRNAs [32]. Nonetheless, miRNA data shown herein could be exploited for future studies to gain more insight into HIV-1 pathogenesis.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our finding is in agreement with a previous study where miR-630 was reported as a biomarker in chronic progressors of HIV-1 [38]. Interestingly, our HM exosomal miRNA data from the South Africa cohort where HIV-1 infected women were carrying HIV-1 load < 1 year (data not shown) showed downregulation of these miRNAs identified in the current study (Table 2 & Suppl Table 1) and correlated with a recent report where it was shown that acute HIV-1 leads to downregulation of miRNAs [32]. Nonetheless, miRNA data shown herein could be exploited for future studies to gain more insight into HIV-1 pathogenesis.…”
Section: Discussionsupporting
confidence: 91%
“…HIV-1 is known to cause dramatic changes in cellular miRNA expression profiles [32][33][34][35], however its effect on HM derived exosomal miRNAs remains to be determined. Here, we first demonstrate the miRNA expression profiling of HM derived exosomes from HIV-1 infected women and describe that HIV-1 significantly altered the expression levels of HM derived exosomal miRNAs in HIV-1 infected women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings on the ability of miR-222 for regulating the expression of PCSK9, a LDLR negative regulator, is in line with its formerly identified roles in lipid metabolic diseases and susceptibility for developing obesity and heart failure. Finally, it has been very recently reported that miR-222 and mir-221 inhibit HIV-1 Entry in Macrophages by Targeting the CD4 Viral Receptor (Lodge et al, 2017 ). Thus, it is possible that miR-221 may also inhibit PCSK9 expression, as the levels of both miR221 and 222 are enhanced by tumor necrosis factor alpha (TNF-α).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they are released into the circulation and have been investigated as potential biomarkers for the diagnosis of different diseases. Substantial evidence exists suggesting HIV/AIDS pathogenesis is modulated by miRNAs (20)(21)(22). Recently, the contribution of miRNAs to diabetic neuropathy as well as other painful peripheral neuropathies has been shown in both clinical and experimental studies (20,23).…”
Section: Introductionmentioning
confidence: 99%